Improving plant disease classification by adaptive minimal ensembling - Bruno, Antonio; Moroni, Davide; Dainelli, Riccardo; Rocchi, Leandro; Morelli, Silvia; Ferrari, Emilio; Toscano, Piero; Martinelli, Massimo (Frontiers in Artificial Intelligence, 2022)
A novel method for improving plant disease classification, a challenging and time-consuming process, is proposed. First, using as baseline EfficientNet, a recent and advanced family of architectures having an excellent accuracy/complexity trade-off, we have introduced, devised and applied refined techniques based on transfer learning, regularization, stratification, weighted metrics and advanced optimizers in order to achieve improved performance. Then, we go further by introducing adaptive minimal ensembling, which is a unique input to the knowledge base of the proposed solution. This represents a leap forward, since it allows improving the accuracy with limited complexity using only two EfficentNet-b0 weak models, performing ensembling on feature vectors by a trainable layer instead of classic aggregation on outputs. To our knowledge, such an approach to ensembling has never been used before in literature. Our method was tested on PlantVillage, a public reference dataset used for benchmarking models’ performances for crop disease diagnostic, considering both its original and augmented versions. We noticeably improved the state of the art by achieving 100% accuracy in both the original and augmented datasets. Results were obtained using PyTorch to train, test, and validate the models; reproducibility is granted by providing exhaustive details, including hyperparameters used in the experimentation. A Web interface is also made publicly available to test the proposed methods.